Ten-Year Poverty Alleviation Effect of the Medical Insurance System on Families With Members Who Have a Non-communicable Disease: Evidence From Heilongjiang Province in China - Xia, Qi; Wu, Lichun; Tian, Wanxin; Miao, Wenqing; Zhang, Xiyu; Xu, Jing; Li, Yuze; Shi, Baoguo; Wang, Nianshi; Yang, Huiying; Huang, Zhipeng; Yang, Huiqi; et al. (Frontiers in Public Health, 2021)
Objective: Non-communicable diseases (NCD) drag the NCD patients’ families to the abyss of poverty. Medical insurance due to weak control over medical expenses and low benefits levels,may have actually contributed to a higher burden of out-of-pocket payments.By making a multi-dimensional calculation on catastrophic health expenditure(CHE) in Heilongjiang Province over ten years, it is significant to find the weak links in the implementation of medical insurance to achieve poverty alleviation. Design:A longitudinal study using a national database. Setting:Data were obtained from the Third, Fourth, and Fifth Health Service Surveys of HeiLongJiang Province. Participants: A sample of 3,820 households with 11,501 individuals in 2003, 5,411 households with 15,571 individuals in 2008, and 5,289 households with 14,431 individuals in 2013. Primary and secondary outcome measures:The study's main variables include CHE, demographic characteristics of household,socio-economic status,illness and health services condition. Results :The average CHE of households dropped from 18.9% in 2003 to 14.9% in 2013.33.2% of the households with 3 or more NCD members suffered CHE in 2013, which was 7.2 times higher than the households without it(4.6%).The uninsured households with cardiovascular disease had CHE of 12.0%, which were nearly 10 percentage points lower than insured households (20.4%-22.4%). For Medical Insurance for Urban Employees Scheme enrolled households, the increasing number of NCD members raised the risk of impoverishment from 3.4% to 20.0% in 2003, and from 0.3% to 3.1 % in 2008. Households with hospital in-patient members were at higher risk of CHE (OR: 3.10-3.56). Conclusions:Healthcare needs and utilization are one of the most significant determinants of CHE.Households with NCD and in-patient members are most vulnerable groups of falling into a poverty trap. The targeting of the NCD groups, the poorest groups, uninsured groups need to be primary considerations in prioritizing services that are contained in medical insurance and poverty alleviation.